2021
DOI: 10.1055/a-1333-2723
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre- and Intraoperative Factors on Endothelial Cell Density in the Early and Late Stage after Penetrating Keratoplasty

Abstract: Aim This retrospective investigated the impact of donor age, recipient age, donor endothelial cell density, vis-à-tergo, and additional intraoperative lens exchange (triple-procedure) on overall early and late phase postoperative endothelial cell density (ECD) following penetrating keratoplasty (PKP) in various diagnosis groups. Patients and Methods In 590 cases with diagnosed keratoconus (KC), Fuchs dystrophy (FD) and herpes simplex virus infection (HSV) who underwent PKP or triple surgery, the ECD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
1
0
2
Order By: Relevance
“…Interestingly, endothelial CD in PKP was, on average, 169.5 ± 32.2 cells/mm 2 higher than in DMEK between the period 6 weeks postoperatively and 1 to 2 years postoperatively (p < 0.001), while the donor endothelial CD of the DMEK group was still higher than that of the PKP group. However, Brand et al (2021) demonstrated in their study that high donor endothelial CD has a positive effect on postoperative endothelial CD (p < 0.001) 16 . Even after 5 years, the CD in the present study was still significantly greater with PKP than with DMEK (p = 0.005).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Interestingly, endothelial CD in PKP was, on average, 169.5 ± 32.2 cells/mm 2 higher than in DMEK between the period 6 weeks postoperatively and 1 to 2 years postoperatively (p < 0.001), while the donor endothelial CD of the DMEK group was still higher than that of the PKP group. However, Brand et al (2021) demonstrated in their study that high donor endothelial CD has a positive effect on postoperative endothelial CD (p < 0.001) 16 . Even after 5 years, the CD in the present study was still significantly greater with PKP than with DMEK (p = 0.005).…”
Section: Discussionmentioning
confidence: 93%
“…Interessanterweise war die Endothelzelldichte bei der PKP zwischen dem Zeitraum 6 Wochen postoperativ und 1 – 2 Jahre postoperativ durchschnittlich um 169,5 ± 32,2 Zellen/mm 2 höher als bei der DMEK (p < 0,001), während die Spenderendothelzelldichte der DMEK-Gruppe noch über derjenigen der PKP-Gruppe lag. Brand et al (2021) wiesen in ihrer Studie jedoch nach, dass eine hohe Spenderendothelzelldichte einen positiven Einfluss auf die postoperative Endothelzelldichte hat (p < 0,001) 16 . Auch nach 5 Jahren war die Zelldichte in der vorliegenden Studie bei der PKP immer noch signifikant größer als bei der DMEK (p = 0,005).…”
Section: Diskussionunclassified
See 1 more Smart Citation